Effect of various dietary nutrient density on the growth performance of local male ducks and their crosse - I.A.K Bintang; M Silalahi; Antawidjaja .; Y.C Raharjo (Indonesian Center for Animal Research and Development (ICARD), 1998)
Three hundred day-old male ducklings were allocated randomly into 12 treatment combinations in 3 x 4 factorial design . Three levels of dietary density ration i.e : Low(12% /2,000 kcal), medium (16%/2,500 kcal) and high (20%/3,000 kcal) and 2 breeds of local ducks Tegal (TT) and Mojosari (MM) and their crossbreds (Tegal x Mojosari (TM) and Mojosari x Tegal (MT)) were applied. Each treatment combination consisted of5 replicates, each of 5 birds. The experiment was carried out for 8 weeks and measurements were weekly feed intake, body weight, weight and/or percentage of carcass, internal organs and abdominal fat. Results indicated that no significant interaction was detected between dietary nutrient density and the breeds of ducks on all parameters measured . Breeds of duck, as well as their crosses did not affect growth performance and other parameters . On the other hand, nutrient density influenced growth performance significantly, except for percentage of carcass and internal organs . In general, feed intake, body weight gain, feed efficiency, carcass weight and abdominal fat of ducks fed low density ration were significantly lower than those fed medium density, which were also lower than those fed high nutrient density diet . Weghtand length of intestine and kidney weight, of ducks fed low density diet however, were higher than the two other treatments . Keywords : Dietary density ration, breeds of duck, growth